Comparative Effectiveness of Different Osteoporosis Medications in Enhancing Bone Mass - Phapasawad, Sitti (Journal of Southeast Asian Orthopaedics, 2025)
Purpose: To compare the spine and non-dominant hip bone mineral density before and after treatment with different categories of osteoporosis medications. Methods: In this retrospective cohort study, we analyzed the medical records of patients with osteoporosis who were prescribed anti-resorptive agents (bisphosphonates, alendronate, risedronate, intravenous ibandronate, and denosumab) or bone-forming agents (teriparatide). Patients were selected using purposive sampling. Descriptive statistical analysis was performed, including calculations of percentages, means, and standard deviations, along with hypothesis testing using Wilcoxon signed-rank and t-tests. Results: Among the 80 participants treated with these medications and monitored over 3–5 years, with at least 2 years of continuous treatment, none had hip or spine fractures. In the bisphosphonate group (n = 59), both the spine and non-dominant hip bone mineral density showed significant improvements. The denosumab group (n = 17) demonstrated a significant increase in spine bone mineral density, whereas the increase in nondominant hip bone mineral density was not significant. The teriparatide group (n = 4) showed improvements in both the spine and non-dominant hip bone mineral density, although not significant, possibly because of the small sample size. Conclusions: All medication categories had positive effects on bone mineral density. Antiresorptive agents, particularly bisphosphonates, showed significant improvements in both spine and hip bone mineral density, whereas denosumab showed significant improvement, specifically in spine bone mineral density. The bone-forming agent teriparatide showed a positive trend, although not significant, likely because of the limited sample size.